Pelatihan Proses Pasteurisasi Sebagai Upaya Menumbuhkan Kemandirian Pemasaran Susu Kambing di Kelompok Sukorejo I, Turi, Sleman - Y. Suranindyah; F. T. Haryadi; D.T. Widayati (ABDIMAS ALTRUIS: Jurnal Pengabdian Kepada Masyarakat, 2018)
The activities of community service which were conducted in Sukorejo, Girikerto, Turi, Sleman aimed to train farmers to be able to produce high quality goat milk, be skillful to process pasteurized milk, and be capable of marketing their dairy products. The activities consisted of counseling and training, focusing on the implementation of hygienic milking procedure and processing pasteurized milk. The community service was carried out in partnership with Plaza Agro, the Faculty of Animal Husbandry of Universitas Gadjah Mada, which is engaged in the sale of dairy and agricultural products. The training materials consisted of lactating goats, stage pens, goat milk, pasteurization and packaging equipment, and chemicals for milk quality testing. Counseling and discussion were done either during farmers meeting or between their activities in the communal goat houses. The program also carried out the procurement of equipment for milk processing and packaging which was facilitated by IbM Ristek Dikti (Higher Education) program 2016. Training results showed that an increase in the number of farmers who implemented hygienic milking, especially on the sanitation aspect, resulting in good quality milk. Density ranged from 1.030 to 1.034 in gravity, 5.5 to 5.6% of fat content and 15.3 to 15.5% of dry matter. The mild had a good flavor, odorless, and without alcohol. The quality of pasteurized milk was good, odorless, and had a typical goat's milk flavor. The reduction time of metylene blue reduction test was 7.9 hours, indicated that the approximate number of bacteria in milk approached 150000/mL, whose average of shelf life was 7 days. Initial marketing of pasteurized goat milk in Plaza Agro was limited on a small scale. The study concluded that processing pasteurized milk was useful for farmers to find an alternative market of goat milk.